Stages of ERP-Based Digital Transformation to Enhance the Competitiveness of the Batik Industry - Ghandara, Reffli; Afrianti, Nursinta; Chrissandhi, Erico Sofyan; Dayani, Camillana Calistaflo (Jurnal Teknik Industri Terintegrasi (JUTIN), 2025)
The batik industry, as part of Indonesia’s cultural heritage, faces significant challenges in the digital era and Industry 4.0. This study analyzes the stages of ERP-based digital transformation in batik SMEs through a case study at Batik Paradise Yogyakarta, designated by the Ministry of Industry as a pilot project in 2024. Using a qualitative descriptive approach with observations, semi-structured interviews, and documentation, the research identifies four implementation phases: (1) preparation and needs analysis, (2) core module implementation, (3) cross-functional integration, and (4) optimization and evaluation. Findings show that ERP adoption enhances operational efficiency, financial transparency, and data integration while supporting cultural preservation through motif and production documentation. The study contributes an adaptive ERP implementation model for batik SMEs and offers policy recommendations to strengthen digital competitiveness.